Pengaruh Penerapan Ideologi Pancasila terhadap Karakter Tanggung Jawab Siswa di SDN 15 Sutijo - Rizki, Arif Aulia; Ananda, Arifan; Kamal, Muhiddinur; Januar, Januar (Lembaga Yasin AlSys, 2024)
This research is motivated by the problem of the low character of responsibility of students at SDN 15 Sutijo, which can be seen from the lack of discipline, punctuality, and lack of responsibility for tasks and the surrounding environment. This phenomenon reflects the urgent need to reinforce the internalization of Pancasila ideological values in education to form better student characters. The purpose of this study was to determine the effect of Pancasila ideology implementation on students' responsibility character at SDN 15 Sutijo. This study used a quantitative approach with a single group experimental research type with pretest - posttest. The population in this study were all students at SDN 15 Sutijo totaling 53 students who also became the sample in this study. Data were collected through questionnaires and analyzed using the paired sample t test. The results of this study found that the application of Pancasila ideology affects the character of student responsibility at SDN 15 Sutijo as evidenced by the results of the t test that the sig value is 0.003 <0.05 and the value of t count is 3.259> t table which is 2.007 and the value > t table which is 3.418> 2.052.